Efficacy of Different Doses of Multiple Micronutrient Powder on Haemoglobin Concentration in Children Aged 6–59 Months in Arusha District. (3rd February 2019) - Kejo, Dyness; Petrucka, Pammla; Martin, Haikael; Mosha, Theobald C. E.; Kimanya, Martin E.
Abstract : In Tanzania's Arusha District, anaemia is a significant public health problem. Recently, home fortification with multiple micronutrient powder was recommended, and daily use of one sachet has shown to be effective. However, it is a challenge for deprived families with low income to afford the daily sachet. The aim of this study was to compare the efficacy of different administration frequencies of micronutrient powder in reducing anaemia in children aged 6–59 months. This research used a community-based, randomized longitudinal trial design with the intent to treat anaemia. Children aged 6 to 59 months (n = 369 ) were randomly assigned to one of four intervention groups which received, on a weekly basis, either five sachets (n = 60 ), three sachets (n = 80 ), two sachets (n = 105 ), or one sachet (n = 124 ) for six months; 310 children completed the study. Using the HemoCue technique, a finger-prick blood was taken at baseline, middle, and end points of the intervention to determine haemoglobin levels. The effect of treatment on haemoglobin was assessed with analysis of covariates with Bonferroni post hoc to test group difference (p > 0.05 ) from each other. At the end, haemoglobin levels were significantly higher in participants who received three or five sachets of micronutrient powder per week compared to those who received one or two micronutrient powder sachets per week (p < 0.05 ). The prevalence of illnesses was reduced from 65% to 30.5% in all groups. This finding indicates that economically challenged families may opt for three times per week sachet administration rather than a more costly daily administration. This trial is registered withPACTR201607001693286 .